2017
DOI: 10.5603/gp.a2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Cytohistological discrepancies of cervico-vaginal smears and HPV status

Abstract: Objectives: Discrepancies between abnormal cervical cytology or high-risk human papillomavirus (HR-HPV) status (cytology negative/HPV positive) and subsequent histological findings are a common occurrence. After using co-testing, the discrepancies between the HR-HPV status and cervical cytology have become an issue. In this study, we aimed to determine the characteristics of women with a discrepancy between histology and cytology/HR-HPV status, in terms of diagnosis, review and identification. Material and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(29 reference statements)
0
8
1
1
Order By: Relevance
“…Poomtavorn et al [20], report the rate of colposcopic cervical biopsy discrepancy as 45.7% with the Pap smear test and the rate of colposcopic directed biopsy histology discrepancy as 29.5% with the Pap smear test. Alanbay et al [21], report that when the level of atypia increases in cervical cytology, cytology-histology consistency rate increases. In our study, while the exact diagnosis of cervical cytology with LEEP was 27.3% for LSIL, this rate increased to 81.8% for HSIL.…”
Section: Discussionmentioning
confidence: 99%
“…Poomtavorn et al [20], report the rate of colposcopic cervical biopsy discrepancy as 45.7% with the Pap smear test and the rate of colposcopic directed biopsy histology discrepancy as 29.5% with the Pap smear test. Alanbay et al [21], report that when the level of atypia increases in cervical cytology, cytology-histology consistency rate increases. In our study, while the exact diagnosis of cervical cytology with LEEP was 27.3% for LSIL, this rate increased to 81.8% for HSIL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the ranges of sensitivities and specificities of cytology and HPV test varied widely 39. In the eligible studies, sensitivities and specificities of cytology ranged from 22.4% to 99.4% and 0.0% to 99.0%, respectively 1234567891011121314151617181920212223242526272829303132333435363738. Therefore, it is useful to assess the diagnostic accuracy of a screening test to predict the presence of SIL and SqCC in the uterine cervix by performing a meta-analysis, including a DTA review.…”
Section: Discussionmentioning
confidence: 99%
“…These tests have contributed to a decrease in the incidence of cervical cancer, especially in geographic areas supported by well-organized screening programs 1. Although several studies have reported on the diagnostic accuracy of the cervico-vaginal smear, results showed a wide range of estimated sensitivity compared to the specificity 1234567891011121314151617181920212223242526272829303132333435363738. Because the diagnostic accuracy can be affected by variable factors, including study time, geographic area, and population,1234567891011121314151617181920212223242526272829303132333435363738 it should be fully elucidated based on these standardized parameters, including the diagnostic grades of cytology.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between the abnormal cervical cytology and histological findings of the specimen obtained by biopsy is reported by other investigators. 24 The sensitivity of cervical cytology versus HPV testing as a triage testing has been investigated for different cervical lesions in order to avoid false negative results and unnecessary invasive procedures due to false positive results. 25,26 There is an ongoing dilemma about the most reliable method that can be used for cervical cancer screening; cervical cytology versus HPV testing.…”
Section: Discussionmentioning
confidence: 99%